Chronic diseases and productivity loss among middle-aged and elderly in India - Shamrin Akhtar; Sanjay K. Mohanty; Rajeev Ranjan Singh; Soumendu Sen (BMC, 2022)
Abstract Context Chronic diseases are growing in India and largely affecting the middle-aged and elderly population; many of them are in working age. Though a large number of studies estimated the out-of-pocket payment and financial catastrophe due to this condition, there are no nationally representative studies on productivity loss due to health problems. This paper examined the pattern and prevalence of productivity loss, due to chronic diseases among middle-aged and elderly in India. Methods We have used a total of 72,250 respondents from the first wave of Longitudinal Ageing Study in India (LASI), conducted in 2017-18. We have used two dependent variables, limiting paid work and ever stopped work due to ill health. We have estimated the age-sex adjusted prevalence of ever stopped working due to ill health and limiting paid work across MPCE quintile and socio- demographic characteristics. Propensity Score Matching (PSM) and logistic regression was used to examine the effect of chronic diseases on both these variables. Findings We estimated that among middle aged adults in 45-64 years, 3,213 individuals accounting to 6.9% (95%CI:6.46-7.24) had ever-stopped work and 6,300 individuals accounting to 22.7% (95% CI: 21.49-23.95) had limiting paid work in India. The proportion of ever-stopped and limiting work due to health problem increased significantly with age and the number of chronic diseases. Limiting paid work is higher among females (25.1%), and in urban areas (24%) whereas ever-stopped is lower among female (5.7%) (95% CI:5.16-6.25 ) and in urban areas (4.9%) (95% CI: 4.20-5.69). The study also found that stroke (21.1%) and neurological or psychiatric problems (18%) were significantly associated with both ever stopped work and limiting paid work. PSM model shows that, those with chronic diseases are 4% and 11% more likely to stop and limit their work respectively. Regression model reveals that more than one chronic conditions had a consistent and significant positive impact on stopping work for over a year (increasing productivity loss) across all three models. Conclusion Individuals having any chronic disease has higher likelihood of ever stopped work and limiting paid work. Promoting awareness, screening and treatment at workplace is recommended to reduce adverse consequences of chronic disease in India.